Tinjauan Post Operative Cognitive Dysfunction (POCD) pada Pasien Geriatri Pasca Anestesi: Perspektif Klinis - Darma Putri, Anak Agung Pranikencana; Kresna Sucandra, I Made Agus; Parami, Pontisomaya (Jurnal Kesmas Asclepius, 2025)
This study aims to determine the incidence and characteristics of POCD in geriatric patients’ post-anesthesia at RSUP Prof. Dr. I.G.N.G. Ngoerah using a descriptive prospective method. The results showed a POCD incidence rate of 60.5%, highest among patients aged ≥70 years. Females experienced POCD more frequently (77.8%) than males (48%). POCD was most prevalent among respondents without formal education (100%). The highest incidence was found in oncology, trauma, and vascular surgeries. Based on duration, the highest POCD occurrence was in medium-duration surgeries (71.4%), followed by major (60%) and minor surgeries (50%). General anesthesia showed a higher POCD incidence (63.6%) compared to regional anesthesia (57.1%). The conclusions of this study emphasize the importance of focusing on geriatric patients, especially those aged ≥70 years, females, and certain surgery types. The implications of this study emphasize the need for safer anesthesia protocols and personalized recovery strategies to reduce the risk of POCD. Keywords: Geriatric, POCD, Post-Anesthesia.